Health information exchange adoption: influences of public insurance programs. (24th September 2021) - Lee, Hsun-Ming; Long, Ju; Mehta, Mayur R.; Zhang, Peiqin
For many years, the US Government has pushed the adoption of health information exchange (HIE), which is a key to spur large-scale innovation in the healthcare delivery. As funding has diminished, healthcare managers need to assess the adoption incentivised by government programs. This study helps to get a better understanding of how the adoption is influenced by the factors associated with the policies regulated by public insurance programs: Medicare and Medicaid. Using the technology-organisation-environment (TOE) framework, we evaluate the health information exchange (HIE) adoption factors associate with policy implications. Based on a dataset integrated from data reported to the healthcare cost report information system and hospital comparison data, we conducted a logistic regression analysis to model the probability of HIE adoption as a function of TOE factors. Besides factors that affect hospital's technology adoption, such as hospital sizes and geographic locations, our research also revealed three significant HIE adoption factors not thoroughly examined before, including imaging efficiency, scale of outpatient departments, and payer mix. Our research could provide insights for practitioners and healthcare managers when examining the strategies associated with HIE adoption.